PERAN GURU PENDIDIKAN AGAMA KRISTEN DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI SEKOLAH - Carinamis Halawa; Peni Nurdiana Hestiningrum; Iswahyudi Iswahyudi (Didache: Jurnal Teologi dan Pendidikan Kristen, 2021)
The formation of the character of these students in an education will affect the development without paying attention to the ethics, character and morals of a student's behavior. So in this case it is very necessary or needed attention from various parties, especially in learning and teaching with the aim of helping students to get to know the world of education from those who don't know to know, especially in knowing the truth of God. As a teacher of Christian religious education, this must be influential in shaping the character in the ethical and moral supervision of students. These students are partially affected by the problem of character crises, because where they are not controlled or uncontrolled in the influence of the development of science and technology, in this case the environmental conditions will be able to affect the character of students. However, in this situation it will be very worrying in shaping that character, not only as parents, teachers, but also as churches in educational institutions. Therefore, as a Christian religious education teacher will be expected to shape the character and morals of students. Therefore, as a teacher, he will be able to carry out his duties with a sense of responsibility in accordance with the objectives of education in learning, namely forming and creating a generation that has noble character, competence, and responsibility in having Christ. As a teacher, he will bring these students to know how an environment is not affected in the formation of character in an education. Christian teachers will play an important role in shaping the character of students who are right and direct in a goal. Pembentukan karakter peserta didik ini dalam suatu pendidikan akan berpengaruh pada perkembangan tanpa memperhatikan etika, karakter serta moral dari suatu perilaku peserta didik. Maka dalam hal ini sangat dibutuhkan atau diperlukan perhatian dari berbagai pihak terkhususnya dalam belajar dan mengajar dengan tujuan supaya menolong siswa untuk mengenal dunia pendidikan dari yang tidak tahu menjadi tahu, terlebih dalam mengenal kebenaran Allah. Sebagai guru pendidikan agama Kristen ini harus berpengaruh dalam membentuk karakter dalam pengawasan etika, dan moral dari peserta didik. Peserta didik ini sebagian mengalami pengaruh dalam masalah krisis karakter, karena dimana mereka tidak terkontrol atau tidak terkendalikan dalam pengaruh perkembangan ilmu pengetahuan dan teknologi, dalam hal ini keadaan lingkungan akan dapat mempengaruhi karakter peserta didik. Akan tetapi, dalam keadaan ini akan sangat mengkuatirkan dalam membentuk karakter tersebut, bukan hanya saja sebagai orang tua, guru, juga sebagai gereja dalam lembaga pendidikan. Oleh karena itu, sebagai guru pendidikan agama Kristen akan diharapkan dalam membentuk karakter dan moral siswa. Maka dari pada itu sebagai guru, akan mampu melaksanakan tugasnya dengan rasa tanggung jawab sesuai dengan tujuan pendidikan dalam pembelajaran yakni membentuk dan menciptakan generasi yang berakhlak mulia, berkompetensi, serta bertanggung jawab dalam memiliki kristus. Sebagai guru akan membawa peserta didik tersebut dalam mengenal bagaimana suatu lingkungan tersebut tidak terpengaruh dalam pembentukan karakter dalam suatu pendidikan. Guru Kristen akan berperan penting dalam membentuk karakter peserta didik yang benar dan mengarahkan dalam suatu tujuan.